Cochlear Implantation in Meniere's Disease: A Systematic Review and Meta‐Analysis. (19th January 2021) - Villavisanis, Dillan F.; Mavrommatis, Maria A.; Berson, Elisa R.; Bellaire, Christopher P.; Rutland, John W.; Fan, Caleb J.; Wanna, George B.; Cosetti, Maura K.
Abstract : Objectives/Hypothesis: Meniere's disease (MD) is a debilitating condition characterized by hearing loss, vertigo, and tinnitus. The objective of this study was to systematically investigate outcomes in MD after cochlear implantation (CoI), with and without labyrinthectomy. Study Design: Systematic review and meta‐analysis. Methods: A systematic review of articles in Medline and Embase was performed to identify all studies of patients with MD who underwent CoI. This analysis evaluates outcomes of speech recognition, pure tone audiometry, vertigo, tinnitus, and quality of life. Results: Of 321 studies identified, 37 were included, involving 216 patients. Mean age at implantation was 61.4 years (range 27–85 years) with average length of follow‐up at 1.7 years (range 0–9 years). Forty‐four (20.4%) patients underwent labyrinthectomy. Meta‐analysis demonstrated significant improvements in audiometric outcomes following CoI. There was a statistically significant improvement in Hearing in Noise Test performance, with a mean difference improvement of 44.7 (95% confidence interval [CI] [8.8, 80.6]) at 6 months and 60.1 (95% CI [35.3, 85.0]) at 12 months. The Freiburger Monosyllabic Test (FMT) and Consonant‐Nucleus‐Consonant (CNC) also improved significantly, with mean difference improvements of 46.2 (95% CI [30.0, 62.4]) for FMT and 19.3 (95% CI [8.1, 30.4]) for CNC. There was a statistically significant decrease in tinnitus, as measured by a mean difference reduction of 48.1 (95% CI [1.0, 95.2]) in the Tinnitus Handicap Index. Conclusions: CoI with and without simultaneous labyrinthectomy is a viable treatment option for patients with MD, yielding high rates of tinnitus suppression and vertigo control. Post‐CoI MD patients demonstrate similar postoperative speech perception outcomes to non‐MD implant recipients. Laryngoscope, 131:1845–1854, 2021